ECSCW 2013: Proceedings of the 13th European Conference on Computer Supported Cooperative Work, 21-25 September 2013, Paphos, C 2013
DOI: 10.1007/978-1-4471-5346-7_11
|View full text |Cite
|
Sign up to set email alerts
|

The Social Life of Tunes: Representing the Aesthetics of Reception

Abstract: I report on two years of participant observation of traditional musicians in Dublin, Ireland. In Irish traditional music, players from all walks of life gather at pub sessions to play tunes together. Due to the ethos of traditional music, the representation of tunes is a constant aesthetic concern. Drawing on the aesthetics of reception, I show how arriving at the proper ''text'' of a tune poses unique challenges. Rather than simply reading notes on sheet music, traditional musicians must imaginatively read th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…TuneTracker is motivated by a two year ethnography of trad musicians in Ireland examining the role of technology in learning the tradition [21]. That field work showed that a common barrier today's amateur musician faces is a misunderstanding of how one ought to properly find and integrate various representations of a tune [17].…”
Section: Tunetrackermentioning
confidence: 99%
See 4 more Smart Citations
“…TuneTracker is motivated by a two year ethnography of trad musicians in Ireland examining the role of technology in learning the tradition [21]. That field work showed that a common barrier today's amateur musician faces is a misunderstanding of how one ought to properly find and integrate various representations of a tune [17].…”
Section: Tunetrackermentioning
confidence: 99%
“…Perhaps the most passioned responses came from musicians who believed that TuneTracker would engender a new kind of amateur player, one who disregards the process of traditional music [21]. Without generalizing, professionals expected that amateurs would not see TuneTracker as a tool, but as a substitute or shortcut to becoming a traditional musician.…”
Section: Creating the Non-traditional Traditional Musicianmentioning
confidence: 99%
See 3 more Smart Citations